Protecting the dharma through calligraphy in Tang China : a study of the Ji Wang shengjiao xu - De Laurentis, Pietro (London : Routledge, 2021)
This is a study of the earliest and finest collated inscription in the history of Chinese calligraphy, the Ji Wang shengjiao xu (Preface to the Sacred Teaching Scriptures Translated by Xuanzang in Wang Xizhi's Collated Characters), which was erected on January 1, 673. The stele records the two texts written by the Tang emperors Taizong (599-649) and Gaozong (628-683) in honor of the monk Xuanzang (d. 664) and the Buddhist scripture Xin jing (Heart Sutra), collated in the semi-cursive characters of the great master of Chinese calligraphy, Wang Xizhi (303-361). It is thus a Buddhist inscription that combines Buddhist authority, political power, and artistic charm in one single monument. The present book reconstructs the multifaceted context in which the stele was devised, aiming at highlighting the specific role calligraphy played in the propagation and protection of Buddhism in medieval China.
Keywords: Ji Wang sheng jiao xu; Buddhist inscriptions -- China; ART / Techniques / Calligraphy; ART / History / General; HISTORY / Asia / China